The relationship between volleyball skills and final ranking in high level men`s volleyball - Drikis, S. A.; Kountouris, P. D. (World Congress of Performance Analysis of Sport VIII, 2008)
For our analysis, we selected the variable which determines the completion of the action and the assignation of the point. We chose to take consideration the variables in terms of the percentage of the total execution of each skill, something that allows us to compare the teams` profile to one another and derive information about the stability of their performance during the championship. Only the variable R#, however, didn`t determine the end of the action and the assignation of the point. We chose to consider R# closely because, from the point of view of many coaches, it is the most important variable for the determination of the final outcome of complex 1 in a volleyball game. We individuate the skill of attack in the two complexes of the game so as to define the role of the importance if the attack both after pass (complex 1) and after a defense (complex 2) for the success of a team. All the variables for attack during complex 1 are important for team`s success. Also the high correlation of P# with PFR(r=, 787) and with AP#(r=, 888) confirm the believe of many coaches that serve`s pass is very important for the success of a men`s team. So the performance of a team in complex 1 is may be considered as very important for its success in a championship. The same concluded from Marelic et al. (2004) in a case study of the performance of only one team. Due to the regulations of volleyball the winning team for a set must serve and play complex 2 at least two times more than its opponent. The ratio of the two variables related with serve (S# and S=) giving a very high correlation with the final ranking(r=-, 816) indicated that is not only important the number of wining or loosing points from serve. For the coach is important to take notice the ratio of lost serves to serve aces. For a multivariate regression analysis (table 3) the two independent variables (AP# and SR) with the higher correlation to PFR giving high coefficient of determination (R2 =, 841) and also good adjusted coefficient of determination (Radj 2=, 806). Conclusively performance in complex 1 is very important for the success of a team. From the skills taking place in complex 2 is important to keep the ratio of lost serves to serves aces as lower as possible and avoid making attack errors.